Phytochemistry of Garcinia rostrata Hassk. ex Hook.f. and Garcinia nervosa Miq. - Wong, Ka Woong (2017)
Garcinia is a plant genus from the family Clusiaceae. The genus Garcinia is known to be a rich source of phenolic compounds like xanthones, benzophenones and flavonoids. These compounds were reported to have good biological activities and they have potential to be drug candidates. Garcinia plants are available in our country especially in Sarawak, and many have still yet to be studied. Literature search indicated no previous reports on chemical compounds from Garcinia rostrata. Large scale extractions of the stem bark of G.rostrata and G.nervosa were conducted using conventional solvent extraction method at room temperature for three days. The isolation and purification of the extracts obtained were carried out by a combination of various chromatographic techniques such as vacuum column chromatography, gravity column chromatography and Thin-layer Chromatography (TLC). The structural elucidations of the pure compounds isolated were assisted by numerous spectroscopic methods including Nuclear Magnetic Resonance (NMR), Gas Chromatography-Mass Spectrometry (GC-MS), Infrared Spectroscopy (IR), Ultra Violet Spectroscopy (UV) and also by comparison with literature data. The crude extracts obtained were tested for their anti-bacterial activities. Phytochemical studies on G.rostrata afford six known xanthones: ananixanthone (42), 6-deoxyjacareubin (43), 6-deoxyisojacareubin (44), 8-deoxygartanin (45), 1,7-dihydroxyxanthone (21) and 1,3,7-trihydoxyxanthone (46) along with two common triterpenoids stigmasterol (24) and β-sitosterol (23). Detail chemical studies on Garcinia nervosa led to isolation of one new xanthone, garnerxanthone (47), three known xanthones: 6-deoxyisojacareubin (44), 1,5-dihydroxyxanthone (20) and 12b-hydroxy-des-D-garcigerrin A (32) as well as two common triterpenoids stigmasterol (24) and β-sitosterol (23). The ethyl acetate extracts of both plants and the acetone extract of G.nervosa showed very significant activities against Bacillus subtilis, Bacillus cereus, Bacillus megaterium and Bacillus pumilus. On the other hand, the acetone extract of G.rostrata showed very significant activities against B.subtilis and B.megaterium. The other extracts showed results comparable to the positive control used against the bacteria tested. Extracts that showed good activities can be used in anti-bacterial formulations.